Factors associated with knowledge and attitudes toward sexual and reproductive health among high school students at Tan Lap High School, Hanoi - Huy, Nguyen Qui; Tu, Tran Doan; Oanh, Nguyen Thi Phuong; Mai, Tran Thi Thanh; Trinh, Ngo Lan; Binh, Nguyen Thanh; Anh, Nguyen Thai; Ngan, Vu Kim (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objective: To identify factors associated with knowledge and attitudes toward sexual and reproductive health among high school students at Tan Lap High School, Hanoi, Vietnam, thereby informing school-based counseling and sexual and reproductive health support for adolescents. Methods: A cross-sectional descriptive study was conducted among 391 students at Tan Lap High School, Hanoi, Vietnam in 2023. Data were collected using a structured self-administered questionnaire through multistage sampling and analyzed using STATA version 16.0. Associations were assessed using the Chi-square test or Fisher’s exact test and logistic regression analysis, with a statistical significance level set at p < 0.05. Results: The proportion of students with adequate knowledge of sexual and reproductive health was 40.2%, whereas 90.0% demonstrated positive attitudes. In multivariable logistic regression analysis, female students were more likely to have adequate knowledge compared to males (AOR = 3.01; 95% CI: 1.82–4.99). Students who discussed sexual and reproductive health had higher odds of adequate knowledge (AOR = 4.61; 95% CI: 2.85–7.45). Students whose fathers were employed in the public sector also had higher odds of adequate knowledge (AOR = 4.11; 95% CI: 1.85–9.12). In univariable analysis, adequate knowledge (OR = 9.33; 95% CI: 2.82–30.88), being female (OR = 2.86; 95% CI: 1.40–5.83) and discussion about sexual and reproductive health (OR = 2.20; 95% CI: 1.04–4.66) were significantly associated with positive attitudes. Conclusion: Knowledge of sexual and reproductive health among high school students remained limited, despite generally positive attitudes. These findings highlight the need to strengthen school-based sexual and reproductive health education and counseling, with involvement of school health staff, primary care providers, and adolescent health counseling services to identify students’ needs and facilitate timely access to appropriate support.